Behavioural Intent of Indian Consumers to Accept Mobile Banking Services - Khalid, Bushra; Sheerin, Aalia (South Asian Journal of Social Sciences and Humanities, 2020)
Banking system around the globe is becoming digitally advanced and India, too, has adopted the  digital mode to transform the payment and settlement system. The number of mobile internet users  is continuously increasing owing to the easy accessibility of mobile phones and cost efficiency of  their usage. Mobile banking allows the consumers to conduct the financial transactions and other  banking activities using mobile phones. Mobile banking has ensured easy and rapid accessibility  of banking facility 24*7 and served as a medium to reach the unbanked, thereby becoming a  gateway to financial inclusion. Digital innovations are critical for achieving and sustaining an  inclusive economic growth, hence, eliminating poverty. In this paper, we have applied the  extended version of the Technology Acceptance Model (TAM), originally given by Davis in 1989,  to study the key determinants of behavioral intent of consumers to accept mobile banking services.  TAM in itself is an adaptation of the Theory of Reasoned Action (TRA) (Fishbien and Ajzen,  1975). According to TRA, the actual action of an individual is determined by his/her behavioral  intention, which, in turn, is influenced by his/her attitude and subject norm. The key constructs  that have been studied in this paper are perceived ease-of-use, perceived usefulness, perceived  credibility, normative pressures, self-efficacy and attitude to use. In order to achieve the objective,  we have adapted a five-point Likert scale questionnaire containing 20items.The behavioral intent  was then regressed against these key constructs. The study attempts to trace the causality between  the behavioral intent and the main key constructs of TAM.
Keywords: Mobile banking; Technology Acceptance Model; Payment and Settlement System; Theory of Reasoned Action; Behavioral Intention.